Ear to the ground. Searching for ourselves in each other - Stok, Witold (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
An acclaimed Polish cinematographer and documentary film director describes his meeting with Sergey Paradjanov in the 1970s in Kiev. Stok found himself there in connection with the shooting of Piotr Studziński’s documentary film about one of Ukraine’s mathematicians. Despite the difficulties created by the Soviet totalitarian state to isolate Paradjanov, Stok managed to reach the director and also to watch his documentary film about the frescoes in Kiev at a special secret club screening. In his essay – a memoir – the author describes the differences between life in the Soviet Union and in more liberal Communist-ruled Poland. He characterizes Paradjanov’s artistic profile and his fate in the Soviet Union.